Structures of social action : studies in conversation analysis - Atkinson, J. Maxwell (John Maxwell); Heritage, John (Studies in emotion and social interaction., 1984)
"Bringing together thirteen original papers by leading American and British researchers, this volume reflects fresh developments in the increasingly influential field of conversation analysis. It begins by outlining the theoretical and methodological foundations of the field and goes on to develop some of the main themes that have emerged from topical empirical research. These include the organisation of preference, topic, non-vocal activities, and apparently spontaneous responses such as laughter and applause. The collection represents the most comprehensive statement yet to be published on this type of research."--Provided by publisher